PENGEMBANGAN MODUL STATISTIK DASAR UNTUK MENINGKATKAN PEMAHAMAN KONSEP ANALISIS STATISTIK PADA MAHASISWA PENDIDIKAN FISIKA UNIVERSITAS MATARAM - Satutik Rahayu (Universitas Pendidikan Mandalika, 2013)
This research aims to develop a learning module to improve the comprehention of basic statistical concepts statistical analysis on physical education students the academic year 2013/2014. This research is a development . 4-D model of development is a model of device development learning . 4-D development model consists of four main stages , namely : 1 . Define , 2 . Design, 3 . Develop and 4 . Disseminate. The subjects of this study were students taking a basic statistics course in semester III . Data analysis using descriptive analysis and percentage . The results showed that the use of learning modules to improve comprehention of the concept is in the category of complete comprehention . While student responses to the learning module used in the results obtained 71.5 % strongly agreed , and 28.5 % agreed .